Danmarks militære aktivisme fortsætter med eller uden USA - Jakobsen, Peter Viggo (Politik, 2015)
It is a widespread misunderstanding that Denmark’s military activism can be explained by American unipo- larity. Denmark began to use its armed forces for activist purposes before the United States became a global power after the end of World War Two. Denmark will not stop its military activism if the United States stops requesting military contributions. e military activism will then continue in cooperation with France, the United Kingdom, the United Nations and the European Union (provided that the Danish opt out on defence is removed). Denmark’s military activism has been underpinned by broad political consensus since the start in 1920 with the Iraq war (2003) as the only exception.